2021
DOI: 10.2147/prbm.s317641
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the COVID-19 Pandemic on the Mental Health and Professional Psychomotor Skills of Dental Students

Abstract: Purpose To estimate dental students’ self-perception of mental well-being (MWB) and its effects on their clinical psychomotor skills (CPS) once they (or their family members) get infected with COVID-19. Materials and Methods This is a cross-sectional (n =268) study from a public dental college in Riyadh. We collected data on MWB and CPS. An 18-item online survey was used to collect the responses from the participants. The inter-rater reliability for the finalised survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…As for dental students, they were already considered one of the most stressed students as a result of the academic pressure, competitiveness and workload [22,23]. Dental students have also suffered from the educational modifications that have occurred during the pandemic, such as the shift to online education to comply with social distancing measures and minimize disease transmission [24]. However, online education cannot fully address the challenges and requirements of dental education, placing dental students under additional stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for dental students, they were already considered one of the most stressed students as a result of the academic pressure, competitiveness and workload [22,23]. Dental students have also suffered from the educational modifications that have occurred during the pandemic, such as the shift to online education to comply with social distancing measures and minimize disease transmission [24]. However, online education cannot fully address the challenges and requirements of dental education, placing dental students under additional stress.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been observed that dental professionals and dental students are the individuals most vulnerable to the risk of COVID-19 transmission [26]. Studies conducted with dental students show that they experience high levels of anxiety during the pandemic as they worry about infecting family and friends [27,28], but more so for those infected with coronavirus [24].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 54 cross‐sectional studies and one case report involving a total of 31,457 participants were included. Ten (18.18%) of the included studies were from India, 14–23 seven (12.72%) from Turkey, 24–30 six (10.9%) from Pakistan, 10,31–35 four (7.27%) each from USA, 6,36–38 Romania, 39–42 Saudi Arabia, 43–46 and Jordan, 9,47–49 two (3.63%) each from Indonesia, 50,51 Brazil, 52,53 and UAE, 54,55 one (1.81%) each from Poland, 56 Iraq, 57 Australasia region, 58 Peru, 59 Germanym, 60 Malaysia, 61 Palestine region, 62 Malta, 63 and Latin‐America region 64 . One (1.81%) study involved participants across several countries including USA, Spain, India, Brazil, Chile, and Ireland 65 …”
Section: Resultsmentioning
confidence: 99%
“… 6 , 29 , 31 Additionally, when students were infected with COVID‐19, their clinical psychomotor skills were four times more affected compared to those who were not infected. 46 …”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 IPC/IPE (collaboration between two or more disciplines within the same profession) and education between primary and secondary care healthcare workers is less well studied, but is becoming important due to the advancing medical/dental technologies and demographical changes, particularly those associated with the COVID-19 pandemic. 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%